2016
DOI: 10.1007/s00251-016-0906-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of killer cell immunoglobulin-like receptor (KIR) genes on susceptibility to HIV-1 infection in the Polish population

Abstract: Killer cell immunoglobulin-like receptors (KIR) are the most polymorphic receptors of natural killer (NK) cells. Their activity diversifies the functions of NK cells in the antiviral immune response, so the presence of certain KIR may affect transmission of HIV-1. The aim of the study was to evaluate the influence of KIR genes on the susceptibility to HIV-1 infection in the Polish population depending on the route of exposure. We determined the frequencies of activating (2DS1, 2DS2, 2DS3, 2DS4f, 2DS4del, 2DS5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…In the early stages of virus infection and development, the elimination of viruses in the body also depends on innate immunity, including NK cells. The killing ability of NK cells carrying KIR2DL2 may be impaired, which has also been verified in studies on KIR2DL2 and HIV (Zwolinska et al 2016). In this study, one possibility is that the inhibition of virus infection mediated by KIR2DL2 can overcome the activation of NK cells by IFN-alpha and decrease the antiviral ability of NK cells.…”
supporting
confidence: 68%
“…In the early stages of virus infection and development, the elimination of viruses in the body also depends on innate immunity, including NK cells. The killing ability of NK cells carrying KIR2DL2 may be impaired, which has also been verified in studies on KIR2DL2 and HIV (Zwolinska et al 2016). In this study, one possibility is that the inhibition of virus infection mediated by KIR2DL2 can overcome the activation of NK cells by IFN-alpha and decrease the antiviral ability of NK cells.…”
supporting
confidence: 68%
“…In this study, KIR2DS5 has been showed as a protective factor for essential hypertension in researched population. As far as we know, KIR2DS5 exhibits an immune activating function either in cytomegalovirus (Alvarado‐Hernandez et al., ) or human immunodeficiency virus‐1 (Zwolinska et al., ) infection, yet in essential hypertension patients, KIR2DS5 plays a protective role. We double checked all data and repeated all experiments; the results of this study still show that some unknown mechanism we did not know about essential hypertension or natural killer cells activating might be hidden and wait for deeply study to discover.…”
Section: Discussionmentioning
confidence: 99%
“…As CF is accompanied by severe infectious lesions of the upper respiratory tract, the treatment of which is far from always effective, it cannot be ruled out, that the genetically induced weakness of the activating receptor site of natural killer cells is affecting this process. It should be noted, that we did not meet such studies in the literature, but based on literary data, which relate mainly to HIV infection [23][24][25] and hepatitis C [26][27][28][29][30], it can be concluded, that the more gentle progression of the disease correlates with increased activation of the functional activity of NK cells.…”
Section: Resultsmentioning
confidence: 89%